Introduction of the flora, life forms and chorology of plants of some regions in western Chabahar (Sistan and Baluchestan Province) - Somayeh Salimi (تاکسونومی و بیوسیستماتیک, 2014)
This study focused on Zarabad, Cheraghabad and Nogombecom plants of sub-basin watershed city of Chabahar, Iran. The studied flora included 78 species which belonged to 66 genera and 29 families. Poaceae with 16 genera and 19 species, Asteraceae with 7 genera and 8 species, Chenopodiaceae with 5 genera and 4 species, Papilionaceae, with 5 genera and 6 species, constituted the largest plant families respectively. The largest genera of the region were: Salsola, Heliotropium and Plantago, respectively. 42% of the flora belonged to Nobo-Sindian elements, 35%to Irano-Turanian, 18%were bioregional elements and 5% of the species were cosmopolitan. Flora of the studied area, included therophytes (56%), chamaephytes (15%), phanerophytes (14%), geophytes (12%) and hemicryptophytes (3%).